2019
DOI: 10.3233/jad-190237
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide Reverts the High-Fat-Diet-Induced Impairment of BDNF Signaling and Inflammatory Response in an Animal Model of Alzheimer’s Disease

Abstract: Background: preclinical, clinical, and epidemiological evidence support the notion that Alzheimer's disease (AD) is a multifactorial condition in which, along with β-amyloid (Aβ) and tau-related pathology, the synergistic activity of genetic, environmental, vascular, metabolic, and inflammatory factors promote the onset and progression of the disease. Epidemiological evidence indicate that glucose intolerance, deficits in insulin secretion or type 2 diabetes mellitus (T2DM) participate in increasing the risk o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 84 publications
2
21
0
Order By: Relevance
“…Petrov et al (Petrov et al, 2015) showed that phosphorylated tau levels were not increased and alterations in cerebral amyloid levels did not play a critical role in memory loss of APP-PS1 transgenic mice when fed HFD from weaning for 6 months. More recently, consistent with our findings, a similar lack of elevated Aβ and phosphorylated tau levels in triple transgenic AD mice were found after 6 months of HFD in older mice and this was associated with no cognitive deficits (Bomba et al, 2019). Furthermore, our data are in agreement with the clinical data.…”
Section: Insulin Deficiency But Not Insulin Resistance Exaggerates supporting
confidence: 93%
“…Petrov et al (Petrov et al, 2015) showed that phosphorylated tau levels were not increased and alterations in cerebral amyloid levels did not play a critical role in memory loss of APP-PS1 transgenic mice when fed HFD from weaning for 6 months. More recently, consistent with our findings, a similar lack of elevated Aβ and phosphorylated tau levels in triple transgenic AD mice were found after 6 months of HFD in older mice and this was associated with no cognitive deficits (Bomba et al, 2019). Furthermore, our data are in agreement with the clinical data.…”
Section: Insulin Deficiency But Not Insulin Resistance Exaggerates supporting
confidence: 93%
“…Indeed, exenatide activates the transcription factor CREB with an increase of BDNF protein expression promoting the activation of neurotrophic pathway and inhibiting apoptosis in a mouse model of age-dependent cognitive dysfunction, potentiating long-term memory (Bomba et al, 2018). Even in a mouse model of AD (the 3xTg-AD undergoing high fat diet), exenatide reverted the impairment of BDNF signaling and neuroinflammation (Bomba et al, 2019).…”
Section: Glp-1ras As Neuroprotective Agents In Neurodegenerative Disementioning
confidence: 99%
“…BDNF is known to be a neurotrophic protective factor, involved in the regulation of several critical neuronal functions and neuroplasticity in patients who suffer nervous system diseases such as Parkinson’s disease, Alzheimer’s disease, and stroke [35,36,37]. Several empirical studies have indicated the benefits of the increased expression of BDNF or receptor in different stages of stroke such as acute ischemic stroke, the rehabilitation process, and recurrence [37,38,39,40].…”
Section: Discussionmentioning
confidence: 99%